Preparation method of methyl functionalized metal-organic framework adsorbent and application of methyl functionalized metal-organic framework adsorbent in gas separation
Through the self-assembly technology of Zn-MOF materials, the problem of uncontrollable traditional adsorbent structure is solved, and low-energy consumption and efficient gas separation is achieved, especially in the field of CO2/CH4 and C2H2/CO2 gas separation, which shows excellent performance. The problems of high energy consumption of gas separation and environmental pollution in the prior art have been solved.
Patent Information
- Application Number
- CN202411495659.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing gas separation process consumes high energy and is harmful to the environment. The molecular structure of traditional adsorbents cannot be controlled, making it difficult to achieve efficient gas separation.
Using Zn-MOF material, the chemical formula is [Zn2(DMA)4(H2TCPB-Me)2], a crystalline material with a periodic network structure is formed by self-assembly, and is used for gas adsorption and separation. The preparation method is simple and the conditions are mild. , has good thermal stability and high specific surface area.
It realizes low energy consumption and efficient gas separation, especially in the field of CO2/CH4 and C2H2/CO2 gas separation, which shows high adsorption selectivity and stability, and is environmentally friendly in the process and low cost.
Smart Images

Figure CN119285979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and specifically relates to a methyl functionalized metal-organic framework adsorbent material, a preparation method thereof, and gas separation application. Background Art
[0002] With the global emphasis on environmental protection and sustainable development, finding and promoting clean and efficient energy has become an urgent need of the times. As an important component of gas resources such as natural gas, biogas, shale gas, and coalbed methane, the development and utilization of methane (CH4) has attracted much attention. However, carbon dioxide gas is often mixed in the extraction process, which will reduce the calorific value of combustion and corrode the gas pipeline, and also limit the scope of utilization. Therefore, it is very important to selectively capture CO2 and achieve efficient separation of CO2 / CH4. Acetylene (C2H2) is an important basic raw material in petrochemical industry. Its production and application play a vital role in social development and scientific and technological progress, and have an immeasurable position. In industry, high-purity acetylene is mainly obtained by cracking hydrocarbon compounds or partial combustion of methane. However, the acetylene obtained by this method contains a large amount of carbon dioxide (CO2) impurity gas, which has a great impact on the quality of the final product in chemical engineering. Therefore, efficient separation of high-purity acetylene is of great significance for improving energy efficiency and reducing production costs.
[0003] The current gas separation processes mainly include chemical absorption, cryogenic distillation and solvent extraction, which are often energy-intensive and have adverse effects on the environment. For example, cryogenic distillation requires the mixed gas to be condensed and liquefied at low temperature, and then distilled and separated in sequence according to the evaporation temperature of different gases, which requires a lot of energy to complete the separation process; while the solvent extraction process is relatively cumbersome and may have residual solvents, posing potential risks to the environment and human health. Therefore, there is an urgent need for a low-energy, environmentally friendly separation and purification process and material.
[0004] Compared with traditional separation technology, adsorption separation can be carried out at room temperature and pressure, with relatively low cost and energy consumption, and has good selectivity for target substances, and can achieve efficient separation; secondly, the adsorption method is simple to operate and low in cost. However, traditional adsorbents, such as zeolite, molecular sieve, and activated carbon, have small surface area and porosity, and their structures cannot be adjusted, making it difficult to achieve gas separation. Metal-Organic Framework (MOF) is a crystalline material with a periodic network structure formed by metal ions and organic ligands through a self-assembly process. MOF has strong applicability in gas adsorption, storage and separation, and selective gas adsorption due to its highly ordered pore structure, large specific surface area, and adjustable and modified pore size. It can be used as a low-energy, high-efficiency, and highly adaptable adsorbent. Summary of the invention
[0005] In order to solve the technical problems in the above-mentioned background technology, the present invention provides a Zn-MOF material
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a Zn-MOF material, the chemical formula is [Zn2(DMA)4(H2TCPB-Me)2], wherein Zn is a divalent zinc ion, H2TCPB-Me is a deprotonated 1,4-di(4-carboxyphenyl)-3,6-dimethylbenzene ligand, and DMA is N,N-dimethylacetamide. The crystal structure of the Zn-MOF material belongs to the triclinic system, the P-1 space group, and its unit cell parameters are the axial length Axis angle α = 92.660(3)°, β = 92.832(2)°, γ = 104.788(3)°, unit cell volume is Z=2.
[0007] The beneficial effects of the present invention are:
[0008] 1. The synthesis method of the Zn-MOF material of the present invention has a simple process, mild conditions, and a yield of 25%-30%. After the reaction raw materials are dissolved, the desired material can be obtained by reacting at about 100°C. There are no toxic or harmful substances and catalysts in all the raw materials used, and no toxic or harmful substances are produced during the preparation process.
[0009] 2. The three-dimensional topological networks of the Zn-MOF material of the present invention are intertwined, and its thermal stability is excellent.
[0010] 3. The Zn-MOF material of the present invention can be used to prepare adsorption materials to achieve adsorption and separation of various gases.
[0011] The crystal structure of the Zn-MOF material of the present invention was tested at 150K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data was received on an EosCCD. A graphite monochromator was used, and λ(Cu Kα) was The data analysis and absorption correction were performed using the CrysAlisPro tool in a variable speed arbitrary angle scanning mode of ω-2θ. All structures were directly solved using the SHELXS program packaged by SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were anisotropically treated, and the hydrogen atoms of the organic ligands were generated by geometric symmetry. The Zn-MOF material structure of the present invention belongs to the triclinic system, P-1 space group, and the basic structural unit of the crystal is obtained by symmetry operation of the asymmetric unit.
[0012] The asymmetric unit consists of two TCPB-Me ligands with two protons removed, two zinc ions, and four N,N-dimethylacetamide molecules.
[0013] The zinc ion is connected to four oxygen atoms in a four-coordinate mode, and these four oxygen atoms come from the oxygen atoms (Zn1: O1, O14; Zn2: O4, O10) in two carboxyl groups of two different ligands (Zn1: O1-C1-O2, O13-C37-O14; Zn2: O3-C36-O4, O9-C55-O10) and two solvent N,N-dimethylacetamide molecules (Zn1: O17, O18; Zn2: O19, O20); each Zn atom center combines with two oxygen atoms from two TCPB-Me ligands and two terminal N,N-dimethylacetamide to form a regular tetrahedron. Each TCPB-Me ligand is connected to two Zn atom centers through its two carboxyl oxygen atoms in the para position.
[0014] The crystal structure of the Zn-MOF material belongs to the triclinic system, P-1 space group, and its unit cell parameters are the axial length Axis angle α = 92.660(3)°, β = 92.832(2)°, γ = 104.788(3)°, unit cell volume is Z=2.
[0015] The present invention also provides a method for preparing a Zn-MOF material, comprising the following steps:
[0016] A. Dissolving H4TCPB-Me ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the H4TCPB-Me ligand to the Zn(NO3)2·6H2O is 1:1, and the concentration of the H4TCPB-Me ligand in the solution is 2.8333 mmol / L;
[0017] B. Add 80 μL of 1:10 nitric acid.
[0018] C. Place the mixed solution in step B in a glass bottle and keep it warm at 100° C. for 24 to 72 hours to obtain the Zn-MOF material.
[0019] The beneficial effects of the present invention are: the preparation method has simple conditions, the reaction can be carried out quickly, energy is saved, and time is saved. In addition, the preparation method of the Zn-MOF material of the present invention has high yield, small amount of ligand used, and cost saving.
[0020] On the basis of the above technical solution, the present invention can also be improved as follows:
[0021] In the present invention, further, the solvent is N,N-dimethylacetamide and water, and the volume ratio is 1:0.1-10.
[0022] The beneficial effect of adopting the above further scheme is that the solvent composed of N,N-dimethylacetamide and water is easily available, inexpensive, and less polluting, and the prepared Zn-MOF material has a better crystal state.
[0023] In the present invention, further, the molar ratio of the H4TCPB ligand to the zinc nitrate hexahydrate is 1:1, and the concentration of the H4TCPB ligand in the solution is 2.8333 mmol / L;
[0024] The beneficial effect of adopting the above further scheme is that the Zn-MOF material obtained by the determined concentration and molar dosage ratio has a better crystal morphology and the reaction is smoother.
[0025] The present invention also provides an application of a Zn-MOF material in the field of low-carbon hydrocarbon gas separation. The Zn-MOF material performs adsorption tests on single-component CO2, C2H2 and CH4 gases to obtain differentiated adsorption amounts of C2H2 / CO2 and CO2 / CH4 for gas separation.
[0026] The beneficial effect of the present invention is that the Zn-MOF material is applied to the field of C2H2 / CO2 and CO2 / CH4 gas separation, making the function of the Zn-MOF material more comprehensive. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a structural diagram of the asymmetric structural unit of the Zn-MOF material of the present invention;
[0028] Figure 2 The structural diagram of the Zn-MOF material of the present invention: (a) the coordination environment of zinc ions; (b) the S-shaped chains arranged in parallel in the formed layer; (c) two connection modes between chains; (d) the pores;
[0029] Figure 3 The XRD spectra of the test and simulation of the Zn-MOF material of the present invention, the abscissa is the Bragg diffraction angle, and the ordinate is the diffraction intensity;
[0030] Figure 4 It is a thermal weight loss curve of the Zn-MOF material of the present invention, the abscissa is the temperature, and the ordinate is the weight loss percentage;
[0031] Figure 5 This is the infrared spectrum of the Zn-MOF material of the present invention, where the abscissa is the wave number and the ordinate is the transmittance;
[0032] Figure 6 This is the N2 adsorption isotherm diagram of the Zn-MOF material of the present invention at 77K, where the abscissa is pressure and the ordinate is the adsorption amount;
[0033] Figure 7 is the pore size distribution curve of the Zn-MOF material of the present invention, the abscissa is the pore size, and the ordinate is the pore size distribution;
[0034] Figure 8 It is the adsorption isotherm diagram of CO2, CH4 and C2H2 of Zn-MOF material of the present invention at 273K, the abscissa is the pressure, and the ordinate is the adsorption amount;
[0035] Fig. 9 It is the adsorption isotherm diagram of CO2, CH4 and C2H2 of Zn-MOF material of the present invention at 298K, the abscissa is the pressure, and the ordinate is the adsorption amount;
[0036] Fig.10 The diagram is the adsorption enthalpy diagram of the Zn-MOF material of the present invention for CO2, CH4 and C2H2, where the abscissa is the adsorption amount and the ordinate is the adsorption enthalpy;
[0037] Fig.11 The adsorption selectivity diagram of the Zn-MOF material of the present invention for C2H2 / CO2 and CO2 / CH4 mixed gases at 273K and 298K, respectively, wherein the abscissa is the pressure and the ordinate is the common logarithm of the selectivity; DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described in detail below in conjunction with implementation. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0039] Example 1
[0040] A method for preparing a Zn-MOF material specifically comprises the following steps:
[0041] A. Accurately weigh 0.0100 g, 0.0170 mmol of 1,2,4,5-tetrakis(4-carboxyphenyl)-3,6-dimethylbenzene (H4TCPB-Me) ligand and 0.0050 g, 0.0168 mmol of zinc nitrate hexahydrate into a reaction container using an analytical balance. At room temperature, add 6 mL of a mixed solvent consisting of N,N-dimethylacetamide and water into the reaction container, wherein the volume ratio of N,N-dimethylacetamide to water is 1:1; then add 80 μL of 1:10 nitric acid;
[0042] B. Place the mixed solution in step A in a glass bottle and keep it in a constant temperature blower at 100° C. for 24 to 72 hours to obtain a colorless crystalline Zn-MOF material.
[0043] like Figure 1 and Figure 2As shown, the colorless crystalline Zn-MOF material was tested at 150K using Agilent's SuperNova micro-focus X-ray single crystal diffractometer, and data was received on an EosCCD. A graphite monochromator was used, and λ(CuKα) was The CrysAlisPro tool was used for data analysis and absorption correction in a variable speed arbitrary angle scanning mode of ω-2θ. All structures were solved directly using the SHELXS program packaged by SHELXTL, and the structure was refined using the SHELXL full matrix least squares method. All non-hydrogen atoms were treated anisotropically, and the hydrogen atoms of the organic ligands were generated by geometric symmetry. The crystal data shown in Table 1, the typical bond length data of the crystal shown in Table 2, and the typical bond angle data of the crystal shown in Table 3 were obtained.
[0044] Table 1: Crystal data
[0045]
[0046]
[0047] Table 2: Typical bond length data of crystals (unit: )
[0048]
[0049]
[0050] Table 3: Typical bond angle data of crystals (unit: °)
[0051]
[0052]
[0053] Combining the crystal data in Table 1, Table 2 and Table 3, the following relevant characterizations of Zn-MOF materials are obtained:
[0054] The asymmetric unit consists of two TCPB-Me ligands with two protons removed, two zinc ions, and four N,N-dimethylacetamide molecules.
[0055] The zinc ion is connected to four oxygen atoms in a four-coordinate mode, and these four oxygen atoms come from the oxygen atoms (Zn1: O1, O14; Zn2: O4, O10) in two carboxyl groups of two different ligands (Zn1: O1-C1-O2, O13-C37-O14; Zn2: O3-C36-O4, O9-C55-O10) and two solvent molecules N,N-dimethylacetamide molecules (Zn1: O17, O18; Zn2: O19, O20).
[0056] The carboxyl groups in the ligand (O1-C1-O2, O13-C37-O14; O3-C36-O4, O9-C55-O10) adopt a monodentate bridging mode to connect adjacent Zn atoms, ultimately forming a [Zn(DMA)2][COO]2 structure. The carboxyl group in TCPB-Me removes two protons and adopts a monodentate bridging mode to connect adjacent Zn atoms, forming a one-dimensional S-shaped chain. These chains are arranged in parallel in the corresponding layer, and the adjacent layer is arranged in parallel in an anti-S shape.
[0057] The Zn-MOF material structure of the present invention belongs to the triclinic system, P-1 space group, and its unit cell parameters are the axial length Axis angle α = 92.660(3)°, β = 92.832(2)°, γ = 104.788(3)°, unit cell volume is Z=2.
[0058] like Figure 3 As shown, the colorless crystalline Zn-MOF material is tested by a powder X-ray diffractometer, the Bragg diffraction angle is 3 to 50°, and the diffraction intensity is measured every 0.01°. The Zn-MOF material exhibits a diffraction pattern as shown in the figure. From the diffraction pattern in the figure, it can be seen that the collected Zn-MOF material has good phase purity.
[0059] like Figure 4 As shown, the colorless crystalline Zn-MOF material was subjected to thermogravimetric analysis. The thermogravimetric test was conducted on a Mettler synchronous thermogravimetric analyzer, machine model RGA / DSC-1, the reaction gas and the protective gas were both nitrogen, the flow rate was 25 mL / min, the running time was 50 minutes, the heating rate was 10°C / min, and the test temperature range was 30-900°C. Figure 4 From the thermogravimetric curve, we can know that the Zn-MOF material can be stable to about 489°C; the complex loses the solvent in the pores before 92°C, the weight loss between 92°C and 400°C is the loss of the coordinated solvent, and the weight loss between 400°C and 489°C is the collapse of the framework. This shows that the Zn-MOF material of the present invention has good stability and can be decomposed at high temperatures.
[0060] like Figure 5 As shown, the colorless crystalline aluminum-based complex was detected by infrared spectroscopy. The infrared test was performed by KBr tablet method and the wavelengths of 4000-400 cm were collected on a Nicolet 330 FTIR spectrometer. -1 Infrared spectrum in the region. Figure 5 It can be seen that the complex is located at 1600cm -1 The absorption peak nearby can be attributed to the stretching vibration peak of the benzene ring skeleton in the ligand, which is located at 1400cm -1The absorption peaks nearby can be attributed to the symmetric stretching vibration peaks of deprotonated carboxyl groups, which are located at 1300-400 cm -1 The absorption peak in the region is a characteristic peak in the fingerprint region of the Zn-MOF material.
[0061] like Figure 6 As shown, the colorless crystalline Zn-MOF material was tested by the ASAP2020 instrument of the American Micromeritics Company. The zinc-based complex exhibited an adsorption isotherm for the single component N2 at 77K as shown in the figure. The adsorption isotherm is a type II isotherm with a very small desorption hysteresis. From the isotherm, it can be obtained that the single-point BET specific surface area of the Zn-MOF material at P / P0=0.2 is 38.804m 2 / g, BET specific surface area is 37.619m 2 / g. The single point value of the total pore volume when P / P0=0.99 is 0.073cm 3 / g; t-plot micropore volume is 0. The pore size distribution is calculated from the N2 adsorption isotherm as follows Figure 7 shown.
[0062] like Figure 8 and Fig. 9 As shown in the figure, the colorless crystalline Zn-MOF material was tested by the ASAP2020 instrument of the American Micromeritics Company. The zinc-based complex exhibited adsorption isotherms for single-component CO2, C2H2 and CH4 gases as shown in the figure. The adsorption amounts of CO2, C2H2 and CH4 at 273K were 22.5 cm 3 / g, 28.8cm 3 / g and 9.4cm 3 / g, the adsorption capacities of CO2, C2H2 and CH4 at 298K are 18.4 cm 3 / g, 25.7cm 3 / g and 5.7cm 3 / g. Therefore, from the differentiated adsorption amounts in the figure, it can be known that the Zn-MOF material can be applied to the gas separation fields of C2H2 / CO2 and CO2 / CH4.
[0063] like Fig.10 As shown, the adsorption enthalpy of the CO2, C2H2 and CH4 adsorption isotherms is calculated using the Virial formula to obtain the relationship curve between the adsorption enthalpy of CO2, C2H2 and CH4 and the adsorption amount. It can be seen from the figure that the maximum adsorption enthalpy of the Zn-MOF material for CO2, C2H2 and CH4 is 29.69 kJ / mol, 47.57 kJ / mol, and 20.82 kJ / mol, respectively.
[0064] like Fig.11As shown, the adsorption selectivity of the Zn-MOF material to CO2, C2H2 and CH4 is analyzed using the ideal adsorption solution theory, and the selectivity-pressure curve shown in the figure is obtained. It can be seen from the figure that the Zn-MOF material C2H2 / CO2 and CO2 / CH4 both have high adsorption selectivity.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A Zn-MOF material, characterized in that: The general chemical formula is [Zn2(DMA)4(H2TCPB-Me)2], where Zn is a divalent zinc ion, H2TCPB-Me is a 1,2,4,5-tetrakis(4-carboxyphenyl)-3,6-xylene ligand with two protons removed, and DMA is an N,N-dimethylacetamide solvent molecule. Each Zn atom center is coordinated with two oxygen atoms from the TCPB ligand and two oxygen atoms from the N,N-dimethylacetamide solvent molecule to form a regular tetrahedron. Each TCPB-Me ligand is connected to two Zn atom centers through its two carboxyl oxygen atoms; The Zn-MOF material structure belongs to the triclinic system, P-1 space group, and its unit cell parameters are the axial length Axis angle α = 92.660(3)°, β = 92.832(2)°, γ = 104.788(3)°, unit cell volume is Z=2.
2. A method for preparing the Zn-MOF material according to claim 1, characterized in that: The steps include: A. dissolving H4TCPB-Me ligand and zinc nitrate hexahydrate in a solvent to obtain a uniform mixed solution, wherein the molar ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:1, and the concentration of the H4TCPB-Me ligand in the solution is 2.8333 mmol / L; B. Add 80 μL of 1:10 nitric acid to step A; C. Place the mixed solution in step B in a glass bottle and keep it warm at 100° C. for 24 to 72 hours to obtain the Zn-MOF material.
3. The method for preparing the zinc-based complex according to claim 2, characterized in that: The solvent consists of N,N-dimethylacetamide and water, and the volume ratio of N,N-dimethylacetamide to water is 1:
1.
4. The method for preparing the Zn-MOF material according to any one of claims 2 or 3, characterized in that: The molar dosage ratio of the H4TCPB-Me ligand to the zinc nitrate hexahydrate is 1:1, and the concentration of the H4TCPB-Me ligand is 2.8333 mmol / L.
5. An application of the Zn-MOF material according to claim 1 in the field of mixed gas separation, characterized in that: The Zn-MOF material was tested for adsorption of single-component CO2, C2H2 and CH4 gases, and the obtained C2H2 / CO2 and CO2 / CH4 adsorption amounts with large differences can be used for gas separation.
Citation Information
Patent Citations
Porous zinc-based MOF material with high thermal stability, and preparation method and application thereof
CN113174054A
Zinc-organic framework material capable of selectively adsorbing carbon dioxide and synthesis method
CN115536857A
Zinc-based metal organic framework material Zn-DPT-PTOBA as well as preparation method and application thereof
CN115894960A
Thorium-based complex, preparation method and application of thorium-based complex in fluorescence detection and low-carbon hydrocarbon separation
CN115947743A
Preparation method and application of flexible metal organic framework material
CN116396489B